2013
DOI: 10.1158/1535-7163.mct-13-0065
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anticancer Activity of Arsenic Trioxide with Erlotinib Is Based on Inhibition of EGFR-Mediated DNA Double-Strand Break Repair

Abstract: Arsenic trioxide (ATO), one of the oldest remedies used in traditional medicine, was recently rediscovered as an anticancer drug and approved for treatment of relapsed acute promyelocytic leukemia. However, its activity against nonhematologic cancers is rather limited so far. Here, we show that inhibition of ATO-mediated EGF receptor (EGFR) activation can be used to potently sensitize diverse solid cancer types against ATO. Thus, combination of ATO and the EGFR inhibitor erlotinib exerted synergistic activity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 50 publications
4
39
0
Order By: Relevance
“…In addition to APL, the antitumor activity of ATO has been reported in a variety of solid tumor cell lines including breast, esophageal, cervical, lung, liver, prostate and liver carcinoma (8)(9)(10)(11)(12)(13). However, it was reported that many solid tumors are less sensitive to ATO than APL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to APL, the antitumor activity of ATO has been reported in a variety of solid tumor cell lines including breast, esophageal, cervical, lung, liver, prostate and liver carcinoma (8)(9)(10)(11)(12)(13). However, it was reported that many solid tumors are less sensitive to ATO than APL.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that ATO induces complete remission in 80-90% of newly diagnosed patients with APL, as well as in 60-90% of all-trans retinoic acid refractory patients (5)(6)(7). Furthermore, the anticancer activity of ATO was also intensively studied in various other hematological malignancies and several solid tumors, including breast cancer (8)(9)(10)(11)(12)(13). Although ATO is very effective in the treatment of APL, ATO has been less successful in other malignancies at tolerable doses.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of ATO alone and its combination with irradiation (IR) on clonogenic survival, cell cycle progression and apoptosis were evaluated in a panel of p53-deficient and -proficient SCCHN cell lines. Since ATO treatment has also been shown to activate the EGFR pathway [17], to interfere with surface EGFR expression levels [18] and to modulate EGFR-mediated DNA double-strand break repair [19] we also assessed the growth-inhibitory activity of ATO in a SCCHN cell line model of acquired cetuximab resistance. In addition, potential cross-resistance between ATO and cisplatin was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…H2AX phosphorylation was clearly induced by these DSBs after 3 h of treatment with CPT [13]. It has been reported that ATO induces DSBs by producing reactive oxygen species (ROS) and forming H2AX phosphorylation and/or DNA fragmentation [40,41]. However, this DNA damage was delayed and was only detectable after 12-24 h. ATO does not induce the formation of topoisomerase I cleavable complex (topo I cc), even though the presence of these complexes reflects alterations of DNA structures induced by caspase-3 activity and ROS-mediated DNA damage [42].…”
Section: Discussionmentioning
confidence: 95%
“…Although the mechanism by which catalytic inhibitors of topoisomerase II induce phosphorylation involves H2AX and the p53 response to DSBs, the details of these mechanisms remain unclear. Moreover, the analogous mechanisms of catalytic inhibitors of topoisomerase I are also poorly characterized, but the formation mechanism of DSBs by treatment with topoisomerase I poison CPT and DNA damaging agent arsenic trioxide (ATO) has been extensively studied [12,16,[40][41][42][43]. H2AX is phosphorylated in response to DNA DSBs [14], and CPT stabilizes the DNA cleavable complex and blocks the subsequent rejoining of DNA breaks.…”
Section: Discussionmentioning
confidence: 99%